Representation of Urban Women and the Loyal Friendship in Bebas (2019) - Luly Prastuty (LPPM Stikosa - AWS, 2022)
Bebas (2019) narrates about a women's friendship that consists of Vina, Kris, Jessica, and Gina, who have been friends since high school, must face the reality that they are from different socio-economy backgrounds when they are adults. This difference may bring them into a latent problem that causes them to compare and rely on, but they unite. The study's objective is to explore women’s representations in an urban Indonesian context film. This research applies Cultural Studies approach using several theories such as Stuart Hall’s representation, film’s mise-en-scène elements, and the girlfriend gaze theory. The analysis will be based on financial ability and family. The result is that there are three constructions about women: women are constructed to be financially stable from being dependent on men, professional women are striving for independent finance, and women are independent but still depend on other women. When women empower each other, there is an indication that they help according to their social class. Vina and Kris seize the highlight because they are wealthy to be dominant as the protagonists for their friends. It can be concluded that the women's friendship in Bebas (2019) was formed because of the powerlessness of women to stand alone, but they are strong together. When they are in a group, women from the upper class has a significant position. Women are constructed powerful when they are in a group. Bebas (2019) can be a form of patriarchy affirmation that forces women to negotiate their positions to empower each other.